Inflation in Developing Countries: Does Central Bank Independence Matter? - Jan-Egbert Sturm; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2001)
We analyse whether central bank independence (CBI) affects inflation in developing countries. For this purpose we have constructed a new data set for the turnover rate (TOR) of central bank governors for a very large sample of countries, which also covers the 1990s. We find that once various control variables are included, the CBI proxy is often not significant. We also conclude that in those regressions in which the CBI proxy is significant, the coefficient of the TOR becomes significant only after high inflation countries are added to the sample.
Keywords: 330; Inflation; central bank independence